Upper Tract Urothelial Carcinoma (Springer New York, 2015)
Upper Tract Urothelial Carcinoma represents the first book of its kind to be dedicated solely to UTUC. Its aim is to improve understanding and eventually care of a disease that is greatly understudied and underappreciated, yet commonly dealt with by many medical and urologic oncologists. The volume features new data regarding genetic susceptibility, gene expression studies and causative factors; contemporary concepts and controversies regarding diagnosis and staging of UTUC; prediction tools and their value in treatment decisions within each disease stage andpatient selection and treatment options such as endoscopic management, distal ureterectomy, radical nephroureterectomy and chemotherapy. Up-to-date information regarding boundaries of surgical resection, indication and extent of lymphadenectomy are covered as well as the role of perioperative/neoadjuvant chemotherapy in patients with high-risk UTUC.   Upper Tract Urothelial Carcinoma will be of great value to all Urologists, Medical Oncologists, and fellows in Urologic Oncology as well as upper level residents in training in Urology and Medical Oncology